Major issues in cognitive aging - Salthouse, Timothy A. (New York ; Oxford : Oxford University Press, 2010)
In recent years the field of cognitive aging has flourished and expanded into many different disciplines. Here, the author tries to identify some of the major phenomena in the field of cognitive aging and discusses issues relevant to the investigation and interpretation of them.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Cognition -- Age factors; Memory -- Age factors; Cognition in old age